STRENGTH AND CONDITIONING PRACTICES OF IRAN Wrestling League STRENGTH AND CONDITIONING COACHES - Far Saeed Jamshidi; Bahman Mirzeai; Arsalan Damirchi (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : The purpose of this study describes the results of a survey of the practices of Iranian Wrestling League strength and conditioning (IWL S&C) coaches. Material: The response rate was 88.5% (100 of 113). The contents survey examines include: (a) background information, (b) physical testing, (c) flexibility development, (d) speed development, (e) plyometrics, (f) strength/power development, (g) unique aspects, and (h) comments from coaches providing additional information. Results: Results indicate, in part, that coaches assess an average of 7.3 parameters of fitness, with tests speed being the most common. All coaches used a variety of flexibility development strategies. Results reveal that all of IWL S&C coaches follow a periodization model. Speed as the first priority (100%) and muscular endurance, power and strength as second priority (97%) of importance in evaluating their athletes. Sixty-six percent coaches (66%) indicated that their athletes used Olympic-style lifts. All coaches employed plyometric exercises with their athletes. Ninety-two percent (92%) of the coaches reported that used plyometric trainings for increasing the speed of their wrestlers and 82% of the coaches used plyometric jump in place exercises as regular practice in their trainings. Conclusions: The squat and its variations, as well as the Olympic-style lifts and their variations, were the most frequently used exercises. The survey serves as a review and a source of applied information and new ideas.